Assessment of Voiding Dysfunction and Nocturnal Enuresis Rates in Primary School Children in an Anatolian City with a Validated Dysfunctional Voiding Scoring System Questionnaire - ŞİMŞEK, FERRUH; TARCAN, TUFAN; TANIDIR, YILÖREN (GALENOS YAYINCILIK, 2018)
Objective: To investigate the prevalence of voiding dysfunction (VD) and nocturnal enuresis (NE) in Turkish primary school children using a previously validated Dysfunctional Voiding Scoring System (DVSS) questionnaire and a self-administered questionnaire. Materials and Methods: The previously validated DVSS questionnaire was completed by the parents of 3015 randomly selected children. Another questionnaire was also administered for studying VD and NE rates, demographic characteristics, and learning or behavioral problems of children. Results: Of all children, 6.6% (n=199) had a score suggesting VD and 6.1% (n=185) had NE. No significant differences were found between children with and without VD in terms of age, gender, and fluid intake. Children with VD had significantly high rates of constipation (19.7% vs 5.2%; p<0.001) and fecal soiling (32.1% vs 5.1%; p<0.01) compared with children without VD. Children with a higher DVSS score had more frequent behavioral or psychological problems (20.7% vs 4.7%; p<0.01) and learning disabilities (14.7 0 M vs 5.5%; p<0.01). VD had no correlation with overall maternal education level and the type of school (government or private). Conclusion: VD and NE are highly frequent in early childhood and positively correlated with children's learning disabilities and psychological problems.
Keywords: Pediatric; Primary school; Symptom score; Voiding dysfunction; DAYTIME URINARY-INCONTINENCE; RISK-FACTORS; PREVALENCE; SYMPTOMS; SCHOOLCHILDREN; POPULATION; BLADDER; STANDARDIZATION; EPIDEMIOLOGY; HABITS